2011 24th International Symposium on Computer-Based Medical Systems (CBMS) 2011
DOI: 10.1109/cbms.2011.5999109
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction from electroencephalograms for Bayesian assessment of newborn brain maturity

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…We will expect that the posterior information on EEG features will be effectively used within this strategy and the ensemble of DTs will be refined by discarding those models which exploit weak features. Similarly to the results obtained in our previous research, we will expect that the proposed strategy will reduce a portion of oversized DT models in the ensemble and the uncertainty in assessment will be decreased Jakaite, Schetinin, & Maple 2008).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…We will expect that the posterior information on EEG features will be effectively used within this strategy and the ensemble of DTs will be refined by discarding those models which exploit weak features. Similarly to the results obtained in our previous research, we will expect that the proposed strategy will reduce a portion of oversized DT models in the ensemble and the uncertainty in assessment will be decreased Jakaite, Schetinin, & Maple 2008).…”
mentioning
confidence: 70%
“…Given a threshold we could find a set of such features and then could refine the ensemble by discarding those DTs which use these weak features. As discussed in (Jakaite, Schetinin, & Maple 2008), gradually increasing a threshold we can discard these DTs while their contribution to the ensemble outcome is negligible. As part of the research we will explore whether such a discarding technique is able to improve the accuracy of Bayesian assessment.…”
Section: Problem Statementmentioning
confidence: 99%
“…К дополнительной ценности 3D-моделирования можно отнести и возможность визуального представления хода оперативного вмешательства для пациента и его семьи, улучшая тем самым взаимосвязь между врачом и пациентом [17]. Дополнительной возможностью метода является оценка индивидуального для пациента риска осложнений [18,19,20]. Получение такой оценки возможно на стадии планирования хирургических вмешательств.…”
Section: Original Research оригинальные исследованияunclassified
“…61 EEG is an important tool for the assessment of brain development in newborns. [62][63][64][65] It has been found that coherent EEG activity during sleep may provide unique insight into maturation processes of brain functional connectivity. Assessments have confirmed that sleep EEG coherence increases across development.…”
Section: Possible Application Areas and Future Workmentioning
confidence: 99%